The Impact of Content Marketing on Purchase Intentions: An Empirical Study of Jamuin.co's Instagram Marketing Strategy - Irwanto Prasetyo; Rashaky Arya Vito; Afara Ross Prawidya; Dhea Putri Aulia; Ridho Satya Dwi Putra; Silvia Nurissaifah; Shofiyatun Khasanah; Maya Aulia Wulan; Devy Mawarnie Puspitasari (International Humanities and Applied Science Journal, 2026)
This study examined the effect of content marketing on consumers’ purchase intentions through Instagram, using Jamuin.co as the research object. The rapid growth of social media usage has encouraged businesses, particularly micro and small enterprises, to adopt content marketing strategies to influence consumer behavior. A causal quantitative approach was employed, and data were collected through an online survey distributed to Instagram users who had previously viewed Jamuin.co’s content. A total of 55 valid responses were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Content marketing was measured based on its relevance, accuracy, value, clarity, accessibility, and consistency, while purchase intention was assessed through consumers’ interest, desire, and willingness to purchase. The results demonstrated that content marketing had a positive and significant effect on purchase intentions, with a path coefficient of 0.736 and a coefficient of determination (R²) of 0.542. This indicates that content marketing explained 54.2% of the variance in consumers’ purchase intentions. The findings confirmed that informative, engaging, and visually appealing Instagram content played a crucial role in shaping consumers’ psychological responses and encouraging purchase intentions. This study provided empirical evidence that effective content marketing strategies on social media could significantly enhance purchase intentions for local brands in the modern herbal beverage industry.